2006
DOI: 10.1111/j.1439-0426.2007.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of the Retina of Chinese Sturgeon (Acipenser sinensis)

Abstract: Vision is an important cue in larval survival to capture prey. Therefore, we examined the development of the retina structure in the Chinese sturgeon (Acipenser sinensis), the density of single cones, the ganglion cells and the nuclei of the outer nuclear layer of newly hatched larvae, covering different developmental stages ranging from hatching (13.3-13.6 mm TL) to 180 days post-hatching (dph) (290.7-301.6 mm TL). At hatching, larvae exhibited an undifferentiated retina. The retina at 3 dph (16.0-16.9 mm TL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Ontogenetic acquisition of rheotaxis in sturgeon prelarvae has been reported to be associated with the morphological differentiation of swimming structures and sensory organs (Dettlaff et al, 1993;Boglione et al, 1999;Chai et al, 2006). The active and robust progress of the rheotacism from this interval is in accordance with morphological developments and differentiations of various fins during this period (Park et al, 2013b;Gisbert and Nam, 2018).…”
Section: Day 5-daymentioning
confidence: 95%
“…Ontogenetic acquisition of rheotaxis in sturgeon prelarvae has been reported to be associated with the morphological differentiation of swimming structures and sensory organs (Dettlaff et al, 1993;Boglione et al, 1999;Chai et al, 2006). The active and robust progress of the rheotacism from this interval is in accordance with morphological developments and differentiations of various fins during this period (Park et al, 2013b;Gisbert and Nam, 2018).…”
Section: Day 5-daymentioning
confidence: 95%
“…However estimates of acuity stemming from behavioural studies are consistently lower than those obtained from anatomical studies of photoreceptor density (Miller et al 1993;Higgs and Fuiman 1996;Job and Bellwood 1996;Ota et al 1999). Although many studies have determined anatomical visual acuity for larval fish (Neave 1984;Margulies 1989;Mas-Riera 1991;Pankhurst et al 1993;Shand 1994;Helvik and Karlsen 1996;Pankhurst and Eagar 1996;Chai et al 2006), studies that pair anatomical measures with behavioural estimates are limited to a few species (Miller et al 1993;Pankhurst 1994;Higgs and Fuiman 1996;Job and Bellwood 1996;Ota et al 1999). In addition, behavioural studies have also shown that improvements in acuity are accompanied by lateral expansion of the visual field (Job and Bellwood 1996;Browman and O'Brien 1992a, b;Cobcroft and Pankhurst 2006), and reduced scotopic thresholds (Fuiman and Delbos 1998).…”
Section: Introductionmentioning
confidence: 94%
“…Since, larval development is a very quickly and complex process (Gisbert et al, 2002), fish larvae prioritize some structures among your initial development, like head and tail (Osse et al, 1997). During this time, the eye is a very important organ for the success in the capture of prey and reception of visual stimuli (Tesser and Portella, 2006), being considered, in some species, a key structural along this period (Chai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%